Simmel’s Adventure and its Relationship to the Ought of Life - Osbaldiston, Nick (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2019)
This paper examines Georg Simmel’s essay “The Adventure” in relation to more recent translations of his later philosophy. Using the foundational framework supplied to us by Simmel, the paper attempts to unpack adventures as moments in our life-course which are timeless in their influence on the self. This transcending of time manifests in the present as emotions attached to the experiences of adventures shape our consideration of the “ought”. Borrowing ideas from the Romantic Wordsworth and incoporating examples from C.S. Lewis and the author’s own life, the article reconsiders the adventure as not simply something experienced and over time forgotten, but as a powerful tool in the reflexive process of understanding relations between “actuality” and “ought” in life.